What are the effects of agricultural management on soil organic carbon in boreo-temperate systems?. Issue 1 (December 2015) - Haddaway, Neal; Hedlund, Katarina; Jackson, Louise; Kätterer, Thomas; Lugato, Emanuele; Thomsen, Ingrid; Jørgensen, Helene; Söderström, Bo
Abstract Background Soils contain the largest stock of organic carbon (C) in terrestrial ecosystems and changes in soil C stocks may significantly affect atmospheric CO2 . A significant part of soil C is present in cultivated soils that occupy about 35 % of the global land surface. Agricultural intensification has led to practices that may decrease soil organic carbon (SOC), and agricultural management has the potential to be a powerful tool for climate change mitigation and increased soil fertility through SOC sequestration. Here, we systematically map evidence relating to the impacts of agricultural management on SOC in arable systems of the warm temperate and snow climate zones (subset of temperate and continental climates: Köppen–Geiger Classification). Methods Seventeen academic citation databases, 3 search engines and 25 organisational websites were searched for literature (academic and grey) using search strings translated into a range of languages relevant to the included geographical scope of the topic. Stakeholders were also contacted with requests for evidence. Bibliographic checking of 127 relevant reviews was undertaken to check for missing articles. Screening for relevance against predefined inclusion criteria was undertaken at title, abstract and full text levels according to a published protocol. All relevant studies were coded in a meta-database describing the citation, study settings, methods and quantitative data available (without extraction of the study findings). A basic critical appraisal of included studies was also performed. A geographical information system (GIS) presenting the map database on a physical, online map was also produced. Results A total of 735 studies from 553 articles was included in the systematic map database. Studies investigated one or more of five broad categories of interventions: amendments (286 studies), crop rotations (238), fertilisers (307), tillage (306), and multiple interventions (55). Studies were identified from across the includible climate zones, with the notable underrepresentation from Russia. The majority of studies employed only point sampling of SOC, low levels of true spatial replication and moderate study periods (i.e. 10–20 years). Missing key methodological information was found in 28 % of studies. Conclusions Long-term study sites identified in this map provide a useful addition to existing databases of long-term experiments (LTEs). The identification of knowledge gaps, such as studies from Russia, also identify a need for improved cataloguing or reporting of existing and on-going research. This systematic map database represents a useful resource for decision-makers wishing to identify knowledge gaps warranting further primary research, knowledge gluts warranting further secondary research, and deficiencies and best practice in research methodology. In addition to the systematic map database, we have also produced two further resources: (1) a database of LTE sites investigating agricultural management and SOC, and (2) a database of reviews and meta-analyses. To our knowledge, this is the first systematic review or map that utilises a GIS for presentation of an evidence base, which we believe substantially increases the utility of the map outputs.